Identifying Priorities for Pre-licensure Nursing Curriculum to Care for People With Intellectual and Developmental Disabilities: A Delphi Study - Don, Anna; Chowdhury, Sushma; Gessese, Selam; Mclean, Jarrod; Zappavigna, Kimberley; Kennedy, Daniel; Rathwell, Amber (Quality Advancement in Nursing Education / Avancées en formation infirmière)

(untitled) (Canadian Association of Schools of Nursing / Association canadienne des écoles de sciences infirmières, 2025)
Background: People with intellectual and developmental disabilities (IDD) experience inequitable health care and outcomes. Pre-licensure nursing programs do not adequately prepare student nurses to care for this population.Purpose: To identify priorities for pre-licensure nursing curriculum content about nursing care for people with IDD.Methods: A three-round, mixed-methods Delphi study, inclusively designed, was administered to nurses and people with IDD. Data were analyzed using descriptive statistics and content analysis.Findings: A total of 16 nurses and 16 people with IDD participated in this study. At the end of the third survey round, consensus had been reached for 77% (10/13) of items under the category of person-centred care, 100% (6/6) of items about communication, 100% (5/5) of items about advocacy, 85.7% (6/7) of items about health and diagnoses, 100% (4/4) of items about collaboration, and 100% (3/3) of items about decision-making.Conclusion: These findings provide nursing faculty with direction for action in IDD-inclusive nursing curriculum. Future studies are needed to explore teaching and learning methods for further implementation.